Portaria PGR/MPU nº 114, de 16 de dezembro de 2016 - Rodrigo Janot Monteiro de Barros (DOU, Brasília, DF, 20 dez. 2016. Seção 1, p. 73., 2016)
Revoga o § 1º do art. 8º da Portaria PGR/MPU nº 34, de 18 de abril de 2016.